Edukasi Buku KIA Meningkatkan Pengetahuan dan Sikap Ibu Dalam pemantauan Tumbuh Kembang Anak di Yogyakarta - Nur Vika, Raisa Dwi; Khofiyah, Nidatul; Sri Daryanti, Menik (Midwifery Care Journal, 2025)
The main factors of child development deviations are knowledge, attitudes and lack of parental skills in early stimulation of child development. Mother's knowledge significantly affects the mother's skills in monitoring and stimulating the development given to her child. Factors such as age, education, and parity also have an influence on parental knowledge related to development. The purpose of this study was to determine the effect of KIA book education on mothers' knowledge and attitudes about monitoring toddler growth and development in the Jetis Health Center work area in Yogyakarta City. Quantitative research using the Pre-Experimental method with a one group pretest-posttest design. The sample used was 96 respondents with systematic random sampling and cluster random sampling techniques and was selected based on inclusion and exclusion criteria. The instrument in this study used a questionnaire on mothers' knowledge and attitudes in monitoring toddler growth and development. Analysis of non-parametric research data using the Wilcoxon-test. The results of the statistical test obtained knowledge results with a p value = 0.000 <0.05 and attitudes with a p-value = 0.000 <0.05 which indicated that there was an effect of KIA book education on mothers' knowledge and attitudes about monitoring toddler growth and development in the Jetis Health Center Work Area in Yogyakarta City. This research is expected to increase mothers' knowledge about toddler growth and development so that they can immediately recognize delays in the toddler growth and development process, so that they can provide comprehensive stimulation as early as possible.